The impact of a health facility construction campaign on health service utilisation and outcomes: analysis of spatially linked survey and facility location data in Ethiopia. Issue 8 (27th August 2020) - Croke, Kevin; Telaye Mengistu, Andualem; O'Connell, Stephen D.; Tafere, Kibrom
Abstract : Background: Access to health facilities in many low-income and middle-income countries remains low, with a strong association between individuals' distance to facilities and health outcomes. Yet plausibly causal estimates of the effects of facility construction programmes are rare. Starting in 2004, more than 2800 government health facilities were built in Ethiopia. This study estimates the impact of this programme on maternal health service utilisation and birth outcomes. Methods: We analyse the impact of Ethiopia's health centre construction programme on health service utilisation and outcomes, using a difference-in-difference design. We match facility opening years to child birth years in four rounds of Demographic and Health Surveys (DHS) using georeferenced data. We also use event study models to test for pre-trends in the outcomes of interest. Results: Opening of new health facilities within 5 km increases facility delivery by 7.2 percentage points (95% CI 5.2 to 9.1) and antenatal care by 0.38 visits (95% CI 0.24 to 0.52). It is not significantly associated with changes in caesarean section births or neonatal mortality. Opening of district hospitals increases facility delivery by 18.2 percentage points (95% CI 12.7 to 23.7), and caesarean section births by 6.8 percentage points (95% CI 2.5 to 11.2), but is not associated with reduction of neonatal mortality. Conclusions: Ethiopia's facility construction program improved access to antenatal and delivery care. However, there was no detectable association between facility construction and neonatal mortality. Increased access to care must be combined with health system quality improvements and broader social development initiatives to sustainably improve health outcomes.